Quarter-wave helicon resonator (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2016)
Introduction. Helicon waves propagates in the magnetized semiconductor plasma. Helicon waves with circular polarization has a nonreciprocal propagation effect and may have a half-wave resonance between faces of parallel plate of semiconductor. Such resonator being coupled with two orthogonal inductor coils becomes a nonreciprocal transformer. This article presents the results of an experimental research of the nonreciprocal transformer based on a modified helicon resonator. Main part. One of the resonator plates is coated with a layer of metal. It is shown, that such resonator becomes quarter-wave. The theoretical basis of the resonance shift is proposed. Experimental results are also presented and discussed. Conclusion. It is shown, that one-side metallization makes possible to reduce the resonant frequency of almost four times, at the same dimensions of the helicon resonator. Furthermore plating improves the heat transfer from the plate of resonator and hence the maximum dissipated power at the same dimensions.